Modelo en dibujo técnico para educación básica con Google Sketch Up - Coral Revelo, Edwin Marcelo (2016)
The min objecino of lis thesis E the proposal of a Model a Mamal Drafing (br Basi Education Googk Sketh Up to bener the educational development of students, th oppornesiy t0.explok their sil, ablies and motivation for the subje is ttesis has been developed according to the guidelines of exploraory research, and is Uerelore of educational type. The main source of primary information are interviews wib experts in Technical Drawing as teachers and professional design , in addiñon to smalerts who are direc inked lo kaming this subject the imerest shown by dem makes us ahink ias his projects aimed foworably as e is aimed at improving. knowedge in an casy lo undersiand. As for the student project is Eivorable also ciltate teachers impart knowiedgs of this subjeot ising dis gromdbrcaking work, making dhe class is benefing educational and entertining irlogy education. “he proposal of his work has done inline about yomg people stan to know tbe detal of the technical drawig in such a way that aims to motivate student Jeaming and have suficiene founiaton for advanced courses hat are not related to dis problem mater, and instead Rel be interest to continue rescaxching and leaming all dat dis axea has to ofér, and wbat is most important lor those who “want to pursue technical careers, so that his project wil encourage úmotonly students but Basic Education vil be extended to al studeres